2015
DOI: 10.1007/s40243-015-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of mesoporous MgO as a potential pre-combustion CO2 sorbent

Abstract: We examined the CO 2 capture capacity of mesoporous MgO (325 mesh size, surface area = 95.08 ± 1.5 m 2 /g) as a potential pre-combustion CO 2 sorbent. Our results show that 96.96 % of MgO was converted to MgCO 3 at 350°C and 10 bars CO 2 pressure. The sorbent could be completely regenerated at 550°C under argon flow. The sorption rate parameters such as surface area and pore size were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The prepared sample showed a high surface area and a high CO 2 adsorption capacity at 200 C. More recently, porous MgO was also used as sorbent for CO 2 capture at intermediate temperatures [18e20]. For instance, Kumar et al examined the CO 2 capture capacity of mesoporous MgO as a potential pre-combustion CO 2 adsorbent [21]. The results showed that 96.96% of MgO was converted to MgCO 3 at 350 C and CO 2 pressure of 10 bar.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared sample showed a high surface area and a high CO 2 adsorption capacity at 200 C. More recently, porous MgO was also used as sorbent for CO 2 capture at intermediate temperatures [18e20]. For instance, Kumar et al examined the CO 2 capture capacity of mesoporous MgO as a potential pre-combustion CO 2 adsorbent [21]. The results showed that 96.96% of MgO was converted to MgCO 3 at 350 C and CO 2 pressure of 10 bar.…”
Section: Introductionmentioning
confidence: 99%
“…That can be related to kinetics limitations. It is clear that water acts as a catalyst in the carbonation process of metal oxides [13,22]. Figure 4 reveals that a considerable amount of siderite can be obtained by 20 h of milling.…”
Section: Iron Ore Carbonation In Mechanochemical Processmentioning
confidence: 98%
“…As it has been shown that carbonation remains very low for MgO samples with low specific surface area even under high CO 2 pressure (10 bars) [11], our carbonation tests were performed using the home-made MgO-T exhibiting a higher specific surface area and pore volume.…”
Section: Reaction Of Mgo With Comentioning
confidence: 99%
“…From the studies of Fagerlund et al [10] and Kumar et al [11] the carbonation of MgO takes place only at high temperature (300°C-350°C) and pressure (10 bar -20 bar) range in the presence of water vapor ( >5%). Otherwise at low or high temperature and atmospheric pressure a small weight gain (less than 8%) can be observed and it is explained by physical or chemical adsorption [12][13][14].…”
Section: Introductionmentioning
confidence: 99%